ETHNICITY AND NATIONALISM: SIPATAHOENAN NEWSPAPER’S VIEWS ON THE NATIONALIST MOVEMENTS IN THE DUTCH EAST INDIES (History Department, Semarang State University and Historian Society of Indonesia, 2018)
This research examines the texts in Sipatahoenan newspaper published by the national movement organization of Paguyuban Pasundan of Tasikmalaya Branch. The focus of the research is how the narrations in Sipatahoenan newspaper show the attitudes towards national issues. The attitudes are worth studying because Paguyuban Pasundan is a national movement organization based on regionalism or ethnicity. The research adopted the historical methodology because it uses historical sources in the form of a newspaper published in the past. The analysis employed critical discourse analysis, postulating that a text is constructed by the elements of ideologies. The ideology here refers to how Sipatahoenan as the newspaper of a national movement organization shows ethnic and nationalist ideologies in addressing some events related to nationalist movements.Â Penelitian ini mengkaji teks koran Sipatahoenan yang diterbitkan oleh organisasi pergerakan kebangsaan Paguyuban Pasundan Cabang Tasikmalaya. Hal yang akan dikaji adalah bagaimana narasi dalam koran Sipatahonen mengandung sikap terhadap isu-isu kebangsaan. Sikap ini menarik dikaji karena Paguyuban Pasundan merupakan organisasi pergerakan kebangsaan yang memiliki dasar kedaerahan atau etnisitas.Metodologi yang digunakan dalam penelitian ini adalah metodologi sejarah karena menggunakan sumber sejarah berupa koran yang terbit di masa lalu. Analisis yang digunakan adalah analisis wacana kritis yang menjelaskan bahwa suatu teks dikonstruksi oleh unsur ideologi yang membuat teks tersebut. Ideologi yang dimaksud dalam penelitian ini adalah bagaimana koran Sipatahoenan sebagai koran organisasi pergerakan kebangsaan memiliki unsur ideologi etnik dan nasionalis dalam mensikapi beberapa peristiwa yang berkenaan dengan pergerakan kebangsaan.Â